THE INTRODUCTION OF INNOVATIVE CONCEPTS IN THE MANAGEMENT SYSTEM OF THE SANATORIUM-RESORT ENTERPRISE IN THE CONTEXT OF ENSURING SOCIO-ECONOMIC SECURITY - BURYK , ZORIANA (Journal of Vasyl Stefanyk Precarpathian National University, 2019)
. Goal. Coverage of introduction of innovative concepts in the system of management of activity of sanatorium and resort enterprises. Research methodology. The following methods were used: analysis (theoretical review of scientific literature on the problem of research); a synthesis that made it possible to integrate individual parts of the facility into a single unit (development of a Balanced Scorecard for health resort enterprises in terms of socio-economic security); benchmarking that allowed us to map concepts (spa marketing, business performance management, and balanced scorecard). Results. The peculiarities of the management system of the sanatorium and resort enterprises in the conditions of social and economic security are considered. It is stated that the concept of management in terms of ensuring the socio-economic security of any enterprise of the sanatorium and resort complex is based on clearly formed systems of organization of management of socio-economic development. The basic methods of implementation, organization and management of social and economic security at the enterprise are distinguished. It is noted that spa marketing is a concept of management of the spa enterprise, which provides a comprehensive study of the needs of clients in the spa treatment and recreation for their fullest satisfaction through complex efforts to produce, sell and promote the spa product in a competitive market with the aim ensuring socio-economic security and profit. The basic processes covered by the concept of Business Performance Management for spa companies are presented. The Balanced Scorecard Balance Scorecard system has been developed for sanatorium and resort enterprises in terms of social and economic security. Scientific novelty. The basic innovative concepts (spa marketing, Business Performance Management and Balanced Scorecard) are proposed, which introduction into the enterprise management system will ensure effective management decisions, achievement of strategic goals, increase of profit and social and economic security in general. Practical importance. The introduction of our proposed concepts into the management system of sanatorium and resort enterprises will provide such an institution with a complete and effective implementation of processes for managing its activities, providing customer service and optimizing the functions and management procedures performed.